2003
DOI: 10.1073/pnas.0437825100
|View full text |Cite
|
Sign up to set email alerts
|

X-inactivation patch size in human female tissue confounds the assessment of tumor clonality

Abstract: Most models of tumorigenesis assume that tumors are monoclonal in origin. This conclusion is based largely on studies using X chromosome-linked markers in females. One important factor, often ignored in such studies, is the distribution of X-inactivated cells in tissues. Because lyonization occurs early in development, many of the progeny of a single embryonic stem cell are grouped together in the adult, forming patches. As polyclonality can be demonstrated only at the borders of X-inactivation patches, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
83
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 20 publications
7
83
0
Order By: Relevance
“…First, for the genetic analysis, we pooled the bulk of the cyst-lining epithelium from each specimen to avoid the bias introduced by the X-inactivation patch size in the assessment of clonality. 42 It is possible that clonal proliferation occurs only focally in some cystadenomas and that the molecular changes in these foci occur in the absence of morphologic alterations that are not detected microscopically. Second, our results do not exclude the possibility that multiple independent clonal events occur in a cyst, which would then result in the erroneous impression of polyclonality.…”
Section: Discussionmentioning
confidence: 99%
“…First, for the genetic analysis, we pooled the bulk of the cyst-lining epithelium from each specimen to avoid the bias introduced by the X-inactivation patch size in the assessment of clonality. 42 It is possible that clonal proliferation occurs only focally in some cystadenomas and that the molecular changes in these foci occur in the absence of morphologic alterations that are not detected microscopically. Second, our results do not exclude the possibility that multiple independent clonal events occur in a cyst, which would then result in the erroneous impression of polyclonality.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the adult colon has large families of adjacent crypts (Ϸ450) (15), which show the same X-linked gene, indicating that after lyonization, early stem cells from the colonic mucosal crypts expand, implicitly by crypt fission, to form large families of related crypts, so far as sharing the same X-chromosome is concerned. However, Kim and Shibata results (17,18) show that the methylation patterns of adjacent crypts diverge markedly by stem cell niche succession, but every 8 years or so, a ''bottleneck'' is reached, where all stem cells in the crypt are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…This proposal would predict that neighboring colonic crypts are closely related to each other. We have previously shown that the X-linked patch in the adult human colon is large, Ϸ450 crypts, so colonic crypts can develop into large families (15). But this does not tell us anything about the development and spread of mutations occurring later in life.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clonality of normal and neoplastic tissue is assessed by the analysis of patches in chimeras or mosaics heterotypic for a clonal lineage marker. The ability to detect polyclonality in early human tumors is restricted by the large patch sizes of X-inactivation mosaics (4). The first indication that familial intestinal adenomas were commonly polyclonal in structure came from a study of a mosaic XY 7 XO male patient with familial adenomatous polyposis (5).…”
mentioning
confidence: 99%